Purity Enhancement of Vinyl Chloride Monomer from Ethylene Dichloride Using Distillation Column Optimization and Recycle Integration - Abdiela Oktafina Alea Putri; Maharani Putri Tungga Dewi; Najwa Af Ida Sofyar; Riani Estu Candraningtyas; Syafa Nisrina Zulfa (Journal of Chemical Engineering Research Progress, 2026)
Vinyl Chloride Monomer (VCM) is a key precursor in the manufacture of polyvinyl chloride (PVC), a polymer of considerable industrial significance. A major synthetic route to VCM involves the reaction of ethylene dichloride (EDC), producing VCM and hydrogen chloride as the principal products. This study aims to enhance the purity of VCM by implementing process improvements through the integration of distillation columns and recycling systems. The optimized configuration achieved an outstanding VCM purity of 99.97%, while simultaneously increasing energy efficiency and minimizing the formation of undesirable by-products. These results underscore the critical importance of advanced reactor design and purification technologies in elevating VCM quality, thereby contributing to more sustainable PVC production within the chemical industry. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).